EFEKTIFITAS PIJAT EFFLEURAGE MENGGUNAKAN MINYAK AROMATERAPI LEMON TERHADAP DISMENOREA PADA REMAJA PUTRI - Sari Permata Gusma; Sri Utami; Darwin Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Dysmenorrhea is menstrual pain that results from an imbalance in the production of progesterone in the blood, resulting in severe pain. The purpose of this research is to determine the effectiveness of effleurage massage with aromatherapy oil for dysmenorrhea adolescents girls. The research design used Quasi Eksperimental with NonEquivalent Control Group. This research conducted in SMPN 1 Ujungbatu, Rokan Hulu towards 34 respondents with 17 people as the experimental group and 17 people as the control group which taken by used non-probability sampling techniques with a type of purposive sampling. The measuring instrument used in both groups is the observation sheet. The analysis used was univariate analysis to determine frequency distribution and bivariate using the alternative test Wilcoxon and Mann-Whitney. The results of this research is the p value (0,000) < α (0,05). This result means that effleurage massage with lemon aromatherapy oil can reduce dysmenorrhea with non pharmacologically which can be practiced independently, this it is expected that students who have other family members or the surrounding community can use effleurage massage with lemon aromatherapy oil. Keywords: adolescents girls, dysmenorrhea, lemon aromatheraoy oil